The Role of Experts in Experts in the Elaboration of the Cape Town Convention: Between Authority and Legitimacy. Issue 6 (1st August 2013) - Devaux, Caroline
Abstract: Globalisation and the development of fast transport and communications have multiplied transnational situations that States, at times, appear ill equipped to handle. Private actors, taking advantage of these new opportunities to claim their authority, are now key actors in the production of transnational law. Since their place in the production process does not have legal grounds, this paper intends to 'transnationalise' the legitimacy discourse by comparing its fundamental criteria to the claim to authority of a particular group of private actors—the aviation experts—during the elaboration of the Cape Town Convention. This article challenges this expertise‐based legitimation process which, despite being grounded on the ability of private actors to develop effective solutions, reveals a limited output and input legitimacy. Finally, the article suggests that the EU is well placed to carry out a legitimacy test to block the reception of undemocratic claims to authority made by influential private actors.